Modified sprouted rice for modulation of curcumin crystallinity and dissolution enhancement by solid dispersion - Luu, Thinh D.; Lee, Beom Jin; Tran, Phuong H.L.; Tran, Thao T.D. (Journal of Pharmaceutical Investigation, 2019)
Sprouted grains, which is a natural polysaccharide, is the subject of increasing scientific interest due to many benefits for human health. The aim of the present work was to develop sprouted rice (SR) as a safe and useful material for application in dissolution enhancement of anticancer poorly water-soluble drugs such as curcumin by solid dispersions (SDs). SDs were prepared with pure SR and modified sprouted rice (MSR) by the melting method. The dissolution rate, drug crystallinity changes, molecular interactions and wettability were characterized and compared between the formulations. The use of MSR could result in a promising system for improving the dissolution rate of poorly water-soluble drugs. MSR could induce a greater amorphous state and improved wettability of drugs for dissolution enhancement compared to SR. Although both SR and MSR showed hydrogen bonding interaction, insignificant differences between SR and MSR were observed. We found that the crystallinity, interactions and wettability of the drug were significantly affected and modulated by MSR.
Keywords: Crystallinity changes; Modified sprouted rice; Molecular interaction; Solid dispersion; Sprouted rice